Techno-economic feasibility analysis of hybrid renewable energy system for off-grid African communities: Insights from a Zambian case study - Satnam Singh Virdy; Francis D. Yamba; Manish Mishra; Isaac N. Simate; Mala Ramesh; Mwansa Kaoma; Edwin Luwaya; Simon Tembo; Shabbir H. Gheewala (Center of Biomass & Renewable Energy (CBIORE), 2026)
As hybrid renewable energy systems are increasingly adopted for rural electrification, this study presents an approach for optimizing off-grid systems in resource-abundant regions. Using a Zambian case study, this study demonstrates actionable insights into the optimal selection and configuration of components for a renewable energy-based off-grid system designed for remote, unelectrified communities with access to solar, wind, and biomass resources. The system's technical, economic, and environmental performance was evaluated through simulation in HOMER Pro software, using various photovoltaic panel ratings (335W, 400W, and 445W), battery technologies (lead-acid, lead-carbon, and lithium-ion), and dispatch strategies (load-following, cycle-charging, predictive-dispatch, and combined-dispatch). Among several configurations, the one featuring a 445W photovoltaic panel and a lithium-ion battery operating under the load-following strategy demonstrated the lowest cost and highest environmental benefits. This configuration resulted in a total lifetime system cost of USD 3.857 million and a levelized cost of electricity of 0.1522 USD per kilowatt-hour, while reducing emissions by 99.9% compared to a diesel-only system. Sensitivity analysis, considering ±20% variations in component costs and discount rate, showed that battery cost had the largest influence, causing a 5 to 12% variation in system cost. These findings suggest that combining high-efficiency solar panels with advanced battery storage and an appropriate dispatch strategy can significantly enhance the affordability and sustainability of off-grid renewable energy systems for rural communities worldwide.